STUDY OF THE QUALITY OF LIFE PATIENTS SUFFERING FROM NERVOUS DISEASES AT DIFFERENT AGE PERIODS IN RESEARCH (American Journal of Interdisciplinary Research and Development, 2023)
The article provides information on the results of research conducted by foreign scientists on the quality of life of stroke patients at different ages.